First record of the alien oriental river prawn Macrobrachium nipponense (De Haan, 1849) in the Euphrates River, Syria. (Latakia University Journal -Biological Sciences Series, 2023)
his study presents the first record of a new species in Syrian freshwater belonging to the Caridea group (Crustacea, Decapoda, Palaemonidae). It is the alian oriental river prawn, Macrobachium nipponense (De Haan, 1849), which is believedto have arrived in the Syrian waters through one of the known methods of species dispersal in aquatic environments, which is difficult to determine in this study. Three individuals were collected from the Euphrates River across from the city of Raqqa in Syria, including two females and one male. The importance of including the male among the samples is meant to assist in the matter of classification, as the taxonomic criteria for this group are related to males more than females. Based on the morphological examination and study of the basic characteristics related to the relative length of the articles of the second pereiopods in adult males, the proportion of the dactylus to the palm of the third pereiopod, the shape of the restrum, the number of teeth on the dorsal and ventral edges, and the color of the body, the studied specimens belong to the species M. nipponense, which began to spread rapidly in Euphrates River Basin. This taxonomic study constitutes a starting point for subsequent studies on this invasive species related to its biological characteristics, its impact on the environment and the food chain, its economic importance, and the method of its introduction and spread in Syrian fresh waters.